Controls on the T Phase Energy Fluxes Recorded on Juan Fernandez Island by Continental Seismic Wave Paths and Nazca Bathymetry - Miguel Sáez; Sergio Ruiz (Geophysical Research Letters)
Abstract T phases from 54 South American earthquakes with Mw > 5.2 are observed at a broadband station on Juan Fernandez Island. We computed the T phase energy flux (TPEF) values of the seismograms. The TPEF values show a large dispersion that can be explained by considering the tectonic characteristics of the South American plate and the Nazca plate bathymetry. The TPEFs generated by the 2015 Illapel and 2017 Valparaíso seismic sequences were controlled by the positions of the interface events along the dip. The central and downdip interplate earthquakes were more efficient in the generation of T phases than the near‐trench interplate earthquakes (depths of <15 km). The variations in the generation efficiency with depth are explained by the continental raypaths of the body waves and the incidence angles of waves entering the sound fixing and ranging channel. Additionally, we observed differences in the TPEFs from both earthquake sequences that were controlled by seamounts atop the Nazca plate along the T phase paths.